Headache a practical manual - Kernick, David; Goadsby, Peter J. (Oxford : Oxford University Press, 2009)
This book is a pragmatic, succinct and authoritative text aimed at GPs, general neurologists and other primary care healthcare professionals dealing with patients with headache. This'Oxford Care Manual' advocates a multi-disciplinary team approach to care.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Headache; Headache -- Treatment